A Line-Surface Integrated Algorithm for Underwater Terrain Matching - Zhang, Lihua; Liu, Xianpeng; Jia, Shuaidong; Shi, Yan (Journal of Geodesy and Geoinformation Science, 2019)
The current underwater terrain surface matching algorithm, which uses Hu moment as the similarity index, cannot gain accurate location due to the algorithm's disadvantage in detecting slight differences. To solve this problem, a line-surface integrated terrain matching algorithm is presented. First, the similarity evaluation method of the traditional Terrain Contour Matching (TERCOM) algorithm is improved, and the strategy used to select the matching regions is developed. Then, a surface matching algorithm based on the geometric similarity is established to determine the optimum match between the reference maps and the actual measured terrains. Finally, a means of “line matching algorithm” and “surface matching algorithm” integration is proposed based on a fixed threshold. The experimental results show that the proposed algorithm can obtain a more accurate location and has greater robustness than that of the surface underwater matching algorithm based on Hu moment.